Karakteristik Kewirausahaan Petani Muda Skala Kecil Berorientasi Pasar - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Yosini Deliana (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
This study aims to identify entrepreneurial characteristics possessed by young farmers. Young farmers who are the object of study are horticulture farmers in Kabupaten Bandung Barat. This study tries to explain the characteristics of farmers in terms of entrepreneurship. This study focuses on young farmers in Cisarua, Parongpong, and Lembang Subdistricts, with land ownership of no more than two hectares (small scale). The determination of the sample is done by a stratified random sampling method. The strata in this study are young farmers under the age of 40 and farming in the sub-sector of horticulture products in Kabupaten Bandung Barat. The next step is to determine the sample in the study as many as 120 farmers. Farmers who play a role as entrepreneurs are not only experts in the production process, but they have visionary results-oriented business managerial skills. The results of the study show that the majority of respondents have moderate (moderate) entrepreneurial characteristics. This is more due to the farming climate in rural areas which is still moderate, not oriented to professionalism and entrepreneurship. However, young farmers have a desire to develop, so that their business processes are different from those of farmers in general, where young farmers are starting to implement professional work methods in their gardens. The entrepreneurial approach has been seen in the way they do business, where they always want to be better, always look for the latest information, create innovations in the garden, apply management in their farming and take risks.